The Influence of Korean Central Government’s Budgeting for Environmental Protection Activities on Environmental Pollution Disputes Coordination - Sa, Yongjin (Advances in Social Sciences Research Journal, 2019)
This study aims to explore the link between government investment for environmental pollution control and environmental pollution disputes. To be specific, this research examined its hypothesis that the mean of percentage of settled petitions against environmental pollution damages in high environmental budgeting years are higher than those in low environmental budgeting years. All data for this research comes from Environmental Statistics Year Book by the Korean Ministry of Environment (1983 2006). To test the hypothesis, this study utilizes a t-test. The empirical result is not consistent with the alternative hypothesis that the mean of percentage of settled petitions against environmental pollution damages in high environmental budgeting years are higher than those in low environmental budgeting years. Also, limitations of this research with suggestions for future research on the environmental pollution and environmental pollution disputes coordination are discussed in this article.